An unusual ocular presentation of histoid leprosy - Patel, Dhara D.; Solanki, Arpita H.; Ganvit, Shankar S. (International Journal Of Community Medicine And Public Health, 2021)
Leprosy is a chronic granulomatous infection caused by mycobacterium leprae, mainly affecting the skin and peripheral nerve. Histoid type of leprosy, which is considered as an extremely rare variant of lepromatous leprosy. We report a case of a 50/year old male presented to our institute with chief complain of conjunctival swelling in both eyes, encroaching over cornea and involving limbus and sclera, associated with painless blurring of vision. An incisional biopsy of the right eye was performed under local anesthesia. Histopathology of right eye biopsy revealed spindle shaped cells having bland looking nuclei and variable amount of cytoplasm which was suggestive of histoid leprosy. A dermatology consultation was sought and patient was diagnosed to have leprosy. Consequent to which he was started on MBALD (multibacillary anti leprosy drug), and showed improvement in patient`s visual acuity as well as regression of right eye swelling and disappearance of left eye swelling.